Relationship between traffic density, metal accumulation, pollution status, and human health problems in adjoining soils and vegetables within the South-South Region of Nigeria - A. Ebong, Godwin; S. Etuk, Helen; B. Anweting, Idongesit; E. Ekot, Anietie; E. Ite, Aniefiok (International Journal of Environment, Agriculture and Biotechnology, 2023)
Road transport is associated with the elevation of trace metals in the adjoining soils and vegetables and rate of metal accumulation on these media is directly related to the traffic density. This research investigated the association between traffic density, metal accumulation, pollution status, and human health problems in adjoining soils and vegetables within the southern Region of Nigeria. Top soils and vegetables (Vernonia amygdalina and Jatropha tanjorensis) were obtained from roadsides along roads with high traffic density namely: Abak, Aka, Ikot Ekpene, Nwanaiba, and Oron. Top soils and vegetables were also obtained from roadside along a road with low traffic density (Ekpri Nsukara) and used as the Controls. These samples and their Controls obtained within Uyo Metropolis using standard procedures were subjected to acceptable analytical treatments and determined the levels of Cd, Cu, Fe, Ni, Pb, and Zn using Spectroscopic methods. Results obtained revealed that, the mean concentrations of these metals in studied soils and vegetables were within their acceptable limits by FAO/WHO. However, higher mean concentrations of these metals were obtained in soils and vegetables from roads with high traffic density than in the Control. Higher mean levels of all the metals were recorded in J. tanjorensis than in V. amygdalina. The contamination factor of the metals in soil varied between moderate and very high contamination classes. The ecological risk factor of the metals ranged from low to the very high risk classes for the respective metals. Potential ecological risk factor revealed very high risks for the metals determined. Higher transfer factors were obtained for J. tanjorensis than V. amygdalina, though below one. Principal component analysis identified one key factor for the accumulation of these metals in the studied soils and vegetables. The metals were within their oral reference doses but, Cd and Pb were above their recommended daily intake limit. The consumption of V. amygdalina and J. tanjorensis exposed the consumers to risks associated with high Cd and Pb, respectively though; the consumers of J. tanjorensis were generally more susceptible to more non-cancer risks. The potential cancer risks associated with the trace metals via the consumption of the studied vegetables varied between the low and moderate cancer risk classes. However, the target cancer risk values obtained for the metals were higher than the threshold risk limit for ILCR < 1 × 10−4 .by USEPA. The total cancer risk revealed that, Cd and Cu were the major carcinogens in the studied vegetables while, the consumers of V. amygdalina have a higher risk of developing cancer than J. Tanjorensis. The study has shown the relationship between road transport and traffic density on the accumulation of metals in soil and vegetables. Health risks associated with the exposure to metals via the consumption of the studied vegetables has also been exposed.